Call for regulation of social media health content: an initiative of the Italian Association of Hospital Dermatologists (ADOI) - Fortunato Cassalia; Andrea Danese; Carmine D'Acunto; Antonio Russo; Corrado Zengarini; Ignazio Stanganelli; Francesco Cusano; Fabrizio Fantini; Salvatore Amato; Davide Melandri; Cesare Massone; Anna Belloni Fortina (PAGEPress Publications, 2024)
Social media platforms have become integral to healthcare communication, particularly in dermatology, where visual assessment and patient education are paramount. While platforms like Instagram, Facebook, and Twitter offer significant opportunities to raise awareness about skin health, promote preventive measures, and encourage early detection of dermatological conditions, the unregulated dissemination of health information poses substantial risks due to misinformation. In response to these challenges, the Italian Association of Hospital Dermatologists (ADOI) has launched a nationwide survey titled "Use of Social Media by Dermatology Professionals: Impact on Public Awareness, Appropriateness of Information, and Correctness of Prevention Messages-An Italian Survey". This initiative aims to analyze social media usage among dermatology professionals, evaluate its impact on public awareness and preventive behaviors, examine the appropriateness and correctness of shared information, identify challenges and opportunities, and assess the need for official guidelines supported by ADOI. The importance of this study lies in its potential to enhance public health outcomes by ensuring that information shared on social media is accurate, evidence-based, and ethically presented. By collecting data-driven insights, the survey seeks to inform the development of professional guidelines, promote responsible digital engagement, and improve patient education and outcomes. Addressing ethical and privacy concerns is also a key objective. The participation of dermatology professionals is crucial in shaping the future of dermatological care and public health education. This initiative represents a critical step toward improving the quality of dermatological information available on social media and ultimately enhancing patient outcomes through better-informed patients and earlier interventions.